2009
DOI: 10.1029/2008jd010752
|View full text |Cite
|
Sign up to set email alerts
|

Ozone photochemical production in urban Shanghai, China: Analysis based on ground level observations

Abstract: [1] Ozone and its precursors were measured from 15 June 2006 to 14 June 2007 at an urban site in Shanghai and used to characterize photochemical oxidant production in this region. During the observation period, ozone displays a seasonal variation with a maximum in spring. Observed nitrogen oxides (NOx) and carbon monoxide (CO) reached a maximum in winter and a minimum in summer. NOx and CO has a similar double-peak diurnal cycle, implying that they are largely of motor vehicle origin. Total nonmethane organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
116
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(134 citation statements)
references
References 58 publications
(80 reference statements)
15
116
0
3
Order By: Relevance
“…In both episodes, the isopleths diagrams clearly indicate that O 3 formation in the city is in a VOC-sensitive (or NO xsaturated) regime where O 3 increases with decreasing NO x but decreases with decreasing VOC. Many studies also reported this regime over different cities (especially their central parts) (Milford et al, 1989;Sillman, 1999, and references therein; Kim Oanh and Zhang, 2004;PCD, 2001;Ran et al, 2009;Torres-Jardon and Keener, 2006). Sillman (1999) pointed to a simple rule to suggest the underlying regime of O 3 formation is to consider morning VOC/NO x ratios, <10 as VOC sensitive and >20 as NO x sensitive.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In both episodes, the isopleths diagrams clearly indicate that O 3 formation in the city is in a VOC-sensitive (or NO xsaturated) regime where O 3 increases with decreasing NO x but decreases with decreasing VOC. Many studies also reported this regime over different cities (especially their central parts) (Milford et al, 1989;Sillman, 1999, and references therein; Kim Oanh and Zhang, 2004;PCD, 2001;Ran et al, 2009;Torres-Jardon and Keener, 2006). Sillman (1999) pointed to a simple rule to suggest the underlying regime of O 3 formation is to consider morning VOC/NO x ratios, <10 as VOC sensitive and >20 as NO x sensitive.…”
Section: Resultsmentioning
confidence: 99%
“…Although it accounts for many chemical and physical processes in the lower atmosphere, its physical representation is simplified and limited, and only gasphase chemistry associated with O 3 is included. OZIPR has been used as a tool to study O 3 , generally at a city scale, for example, in Jiang et al (1997); Tonnesen (1999); Tang et al (2008) ;Milt et al (2009);Ran et al (2009), andOrlando et al (2010). Two basic modes of simulation available by the model are (1) moving trajectory and (2) city-wide (i.e., stationary box).…”
Section: Photochemical Box Model and Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In the period 2005-2012 the greatest number of measurements of O 3 and NO x ranged from 0 to 40 µg · m -3 , which was different than Nidzgorska-Lencewicz [35] showed for Szczecin, Poland. A large variation in tropospheric O 3 , a secondary pollutant, is associated mainly with the differences in weather conditions in Poland in consecutive years and the content of ozone precursors, eg nitrogen oxides [1,7].…”
Section: Discussionmentioning
confidence: 99%
“…As key precursors of the O3 formation (Fujita, 2001;Geng et al, 2008;Ran et al, 2009;Lyu et al, 2016), VOCs also exhibit detrimental effects on human 5 health (Colman Lerner et al, 2012;He et al, 2015) and air quality.…”
Section: Introductionmentioning
confidence: 99%